Internal control in the execution of works by direct administration in a local government of Peru - Huayra Romero, Oswaldo (2023)
Objective. The objective of the study was to determine the relationship between internal control and the execution of works by direct administration in the District Municipality of Santa María del Valle, Huanuco, 2019. Methods. For it, a census sample composed of a total of 20 municipal collaborators was used. The research methodology used was applied, with a quantitative approach and a correlational descriptive level. A non-experimental and cross-sectional design was used. To obtain information from the population, the survey and questionnaire were used as a technique and instrument, respectively. The questionnaire was validated through experts judgment and demonstrated high reliability with a Cronbach alpha coefficient of 0.92. Results. The main result of the study revealed that there is a direct and significant relationship between internal control and the execution of works by direct administration (0.471). The risk assessment dimension also shows a direct and significant relationship (0.471). Similarly, the dimension of management control activities is directly and significant related. Conclusions. In conclusion, is confirmed the existence of a significant and direct relationship between "internal control" and the "execution of works by direct administration" in the District Municipality of Santa María del Valle, Huanuco, 2019.